Proceedings of the 9th Annual Dubai Medical Education Symposium 2015. Issue 2 (May 2016) - Shersad, Fouzia; Sheikh, Hajer; Aldoori, Munther; Ahmed, Mohammed; Muscat-Baron, Joseph; Abdelmannan, Dima; Hamdy, Hossam; Raza, Syed; Kumar, Parveen; Bayoumy, Fatheia; Pelizzo, Gloria; Irani, Mike; et al.
Table of content I1 The 9th Annual Dubai Medical Education Symposium 2015 addresses the recent strides in medical education and clinical practice Fouzia Shersad, Hajer Sheikh S1 Acute lower limb ischaemia — Snow White and the Seven "Ps" Munther I. Aldoori S2 Learning styles in medical education Mohammed Galal El Din Ahmed S3 Reflection and feedback in teaching in clinical settings Joseph Michael Muscat-Baron S4 Medical Education in the Millennial Era Dima Abdelmannan S5 Current trends in the assessment of clinical competency at the workplace Hossam Hamdy S6 Influence of culture in delivering education Syed Tanzeem Haider Raza S7 Medical education – its day-to-day value in caring for patient Parveen J Kumar S8 IgG-4 related diseases (IgG-4 RD): what the clinician needs to know Fatheia Ali Bayoumy S9 From fetus to infant: the pediatric surgical care come into its own Gloria Pelizzo S10 20 minutes to know rheumatic disease Mike Irani S11 Research trends at Dubai Medical College Fouzia Shersad, Doaa Sultan P1 The Clinical Skills & Simulation Center (CSSC): Facing challenges in implementing the standardized program during OSCE (Objective Structured Clinical Examination) for undergraduate medical students Sumaiah Ali Abdulwahab P2 Informed consent education in a multicultural medical environment: clinical clerks' perspectives Tahra AlMahmoud, M. Jawad Hashim, Margaret Ann Elzubeir, Frank Branicki P3 Effectiveness of information literacy on the information retrieval activity of medical students Bushra Parveen P4 Opportunistic infections in AIDS R. Subha Parameshwaran, Shubhangi Pathak P5 From transactional to transformative learning: engaging early-stage students in community engagement activities Ghazala Khan, Sabeena Salam, Nabeerah Aftab P6 A study of drug utilization of over the counter (OTC) drugs in private pharmacies of a residential area of Dubai, UAE Tasneem Sandozi, Aksha Memon, Maira Khalid Mehmood, Nayyab Mohammed Tayyab Mustafa, Almas Parker, Kawther Hamdi P7 General education matters for envisioning holistic integrative thinking in healthcare professionals Sabeena Salam P8 Course report: multidimensional imaging and capturing the quality of offered courses Eman Abu-Gharbieh, Sabeena Salam P9 Recent advances in medical education M. Jawad Hashim